Optimizing frass and PGPR on the growth and yield of kailan (Brassica oleracea) - Undang Undang; Elya Hartini; Wafa Fauziah; Ristina Siti Sundari; Farhan Ahmad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Plant growth-promoting rhizobacteria (PGPR) and frass application have drawn interest as ways to increase plant productivity. This research aimed to evaluate the effect of frass and PGPR application on the growth and yield of kailan. The effects of varying frass dosages/F (0, 15, 20, and 25 tons ha-1) and PGPR concentrations/P (0, 5, and 12.5 mL L-1) on plant height, leaf number, leaf area, scaffold weight, and leaf weight per plant at 14, 21, and 28 days after planting (DAP) were examined. The growth of plants was generally enhanced by increasing dosages of frass and PGPR. The treatment F25P5 consistently produced the best results across all parameters, demonstrating its effectiveness in enhancing plant growth and yield. Positive correlations between plant height, leaf area, and leaf weight per plant (0.99) were found using correlation analysis, suggesting that leaf expansion is essential for biomass accumulation. Plant height, leaf number, and biomass-related parameters clustered together, confirming their interdependence in growth, and principal component analysis (PCA) showed that PC1 explained 94.09% of the variance. The results highlight that while excessive doses of frass and PGPR may have declining effects, balanced treatments significantly increase plant productivity. Optimizing the dosage of Frass and Rhizobia is crucial to achieving the best results for Brassica oleracea. Frass 25 tons ha-1 and PGPR 5 mL L-1 appear to be the most effective treatment. Keywords: biofertilization; ecofriendly fertilization; Rhizobacteria